A description of liver and blood changes in matrinxã (Brycon amazonicus) during induced spawning - Zanuzzo, Fábio S. [UNESP]; Oda, Gustavo M. [UNESP]; Hoshiba, Marcio A. [UNESP]; Senhorini, José A.; Zaiden, Sérgio F.; Urbinati, Elisabeth C. [UNESP] (Elsevier, 2018)
We investigated the effects of induced spawning on liver and blood cell changes in matrinxã breeders, a commercially valuable South American fish that requires hormonal manipulation and stripping to spawn, a trait shared by other important aquaculture species. Little attention has been given to this topic despite the mortality rates commonly reported by fish farmers following this practice. In this study, we show that the overall handling required in induced spawning severely impaired the liver (hypertrophy of the hepatocytes, enlargement of the cell nuclei and reductions of glycogen deposits) which was mainly attributed to hormonal therapy. Additionally, the induced spawning procedure increased the number of red blood cells and decreased the white blood cell and thrombocyte count. These results corroborate the stressful conditions and immunosuppression, which together with the liver damage may explain the reported mortality rates. Finally, our findings outline important approaches for improving induced spawning technique.
Keywords: Brycon amazonicus; Hormonal therapy; Induced spawning; Liver damage; Stress